Complex forensic medical evaluation of the traumatic brain injury: case of practice - Svіtlana Diachenko; Roksolana Dіduk; Nailia Kashapova; Alina Pletenetska (Bogomolets National Medical University, 2021)
The problem of studying the mechanisms of the occurrence of traumatic brain injury remains a very urgent issue for forensic medicine. The high incidence and high mortality rate of head injuries underlines its importance to experts. The article presents a case from the practice of a forensic medical examination of a traumatic brain injury. This case is indicative, since it clearly demonstrates the difficulties that forensic doctors face when examining craniocerebral injuries, when determining the mechanism of damage and the severity of bodily injuries. In this case, there is damage to the head and a concussion. The cited several conclusions of the experts of the bureau of forensic medical examination and the commission examination of the Main Bureau of Forensic Medical Examination of the Ministry of Health of Ukraine regarding the forensic medical assessment in the case of traumatic brain injury with damage to the head. When conducting an investigative experiment, it was determined that the simultaneous occurrence of an abrasion and a concussion of the brain with one traumatic effect in the glabellar region is unlikely. After all, a concussion of the brain and abrasions in the glabellar area were formed by different mechanisms. The results of this assessment of the characteristics of traumatic brain injury can be useful for preventing difficulties in establishing the mechanism of damage in further expert practice.